2022
DOI: 10.1007/s42452-022-05114-9
|View full text |Cite
|
Sign up to set email alerts
|

Tool wear mechanism, monitoring and remaining useful life (RUL) technology based on big data: a review

Abstract: Tool wear is a key factor affecting many aspects of metal cutting machining, including surface quality, machining efficiency and tool life. As machining continues to evolve towards intelligence, hot spots and trends in tool wear-related research are also changing. However, in the current research on tool wear, there are still no recognized most effective tool wear suppression methods, signals are easily disturbed, low efficiency of signal processing methods and poor model generalization ability, etc. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…When we obtain all the predicted values x (t n ) corresponding to t n , we have to perform the backward propagation process. The first step is the construction of the loss function, as shown in equation (10),…”
Section: Model Training: Backward Propagation Of Neural Odementioning
confidence: 99%
See 1 more Smart Citation
“…When we obtain all the predicted values x (t n ) corresponding to t n , we have to perform the backward propagation process. The first step is the construction of the loss function, as shown in equation (10),…”
Section: Model Training: Backward Propagation Of Neural Odementioning
confidence: 99%
“…The common nonlinear signal processing methods are mainly: empirical modal decomposition (EMD) and variational modal decomposition (VMD). EMD is capable of automatically processing non-smooth signals, and many scholars have applied it to the extraction of tool wear features [10]. However, its components are prone to modal confounding [11].…”
Section: Introductionmentioning
confidence: 99%
“…Since tool wear is a key factor influencing the CFRP drilling operations, its monitoring and control are of vital importance to the current manufacturing sectors. Tool wear monitoring can be roughly divided into direct and indirect monitoring (Zhou et al, 2022). Direct measurements mainly involve the optical image method, the contact resistance method and the radiometric method.…”
Section: Wear Effects and Monitoringmentioning
confidence: 99%
“…However, these methods require a stoppage to detect the tool and have no real-time monitoring function. The measurement results are also affected by cutting fluids, lighting and chips (Zhou et al, 2022). In contrast, the indirect measurement method uses the effect of the state of the tool when it is worn or about to break with specific working parameters.…”
Section: Wear Effects and Monitoringmentioning
confidence: 99%
“…On the other hand, the techniques used for processing the information obtained for the identification, evaluation or prediction of cutting tool wear are varied. Several literature reviews have identified the main techniques, tools and trends for processing [21][22][23][24]. Firstly, signals are processed directly in the time domain [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] or techniques or transforms are used for their analyses in the frequency [3,5,[18][19][20] or time-frequency [19,20] domains.…”
Section: Introductionmentioning
confidence: 99%